Konstruksi Kesejahteraan Psikologis Masyarakat melalui Nilai-Nilai Budaya Lokal: Perspektif Psikologi Sosial dan Sosiologi Budaya - Rezky Graha Pratiwi; Irwan Irwan (Jurnal Ilmiah Psyche, 2026)
This study aimed to analyze the construction of psychological well-being through local cultural values among communities in Puding Besar District, Bangka Regency, Indonesia, using perspectives from social psychology and cultural sociology. The study employed a qualitative approach with an interpretative phenomenological design. Participants consisted of 15 community members selected through purposive sampling based on their active involvement in local social and cultural activities. Additional key informants included community leaders, religious leaders, traditional leaders, and village officials. Data were collected through in-depth interviews, participant observation, and document analysis. The data were analyzed using Interpretative Phenomenological Analysis (IPA), involving coding, theme identification, and interpretation of participants’ lived experiences. The findings revealed five major themes contributing to psychological well-being: local culture as a source of identity and meaning in life, mutual cooperation as a mechanism of psychosocial support, kinship relationships as a foundation of emotional security, togetherness as a promoter of social cohesion, and cultural preservation as a form of self-actualization and sustainable well-being. The study concludes that psychological well-being is a socio-cultural construct shaped through the internalization of local cultural values that strengthen identity, social capital, emotional support, and meaning in life within the community.